Smart Youth Doing Digitalization Solution (SDGS) Innovation as a Human Resource Empowerment Strategy: A Case Study of Cafe Sawah, Village-Owned Enterprise Pujon Kidul - Bangun, M. Fitrah Ashary; Tuasikal, Dita Fomara; Muhammad, Beta Arif (Buletin Ekonomika Pembangunan, 2025)
This study aims to examine and optimize human resource management at Cafe Sawah, a business unit of the Village-Owned Enterprise (BUMDes) in Pujon Kidul Village, by implementing digital innovation to address the challenges of the Industrial Revolution 4.0. The research background arises from the employees' limited digital capabilities, which negatively impact service quality while recognizing digital transformation's vast opportunities in the modern era. The novelty of this study lies in developing the SDGS (Smart Youth Doing Digitalization Solution) program, which integrates basic digital training, a branding challenge through the Cafe Sawah Challenge (CSC), and an innovative ordering system called Click order. This research fills a gap in the literature on human resource management in rural tourism by proposing applicable and practical training and development methods. The study employs SWOT analysis, empirical surveys of visitors, and field studies to obtain actual data on human resource conditions and technology implementation. The findings indicate a significant improvement in employee competencies and operational efficiency, positively impacting Cafe Sawah's competitiveness and brand image. The study concludes that digital innovation is a strategic solution for human resource empowerment in the digitalization era.Keywords: Digitalization, Cafe Sawah, BUMDes, Industrial Revolution 4.0, SDGs